Brain Phosphorus Magnetic Resonance Spectroscopy Imaging of Sleep Homeostasis and Restoration in Drug Dependence. (2007) - Trksak, George H.; Jensen, J. Eric; Renshaw, Perry F.; Lukas, Scott E.
Abstract : Numerous reports have documented a high occurrence of sleep difficulties in drug-dependent populations, prompting researchers to characterize sleep profiles and physiology in drug abusing populations. This mini-review examines studies indicating that drug-dependent populations exhibit alterations in sleep homeostatic and restoration processes in response to sleep deprivation. Sleep deprivation is a principal sleep research tool that results in marked physiological challenge, which provides a means to examine sleep homeostatic processes in response to extended wakefulness. A report from our laboratory demonstrated that following recovery sleep from sleep deprivation, brain high-energy phosphates particularly beta–nucleoside triphosphate (beta-NTP) are markedly increased as measured with phosphorus magnetic resonance spectroscopy (MRS). A more recent study examined the effects of sleep deprivation in opiate-dependent methadone-maintained (MM) subjects. The study demonstrated increases in brain beta-NTP following recovery sleep. Interestingly, these increases were of a markedly greater magnitude in MM subjects compared to control subjects. A similar study examined sleep deprivation in cocaine-dependent subjects demonstrating that cocaine-dependent subjects exhibit greater increases in brain beta-NTP following recovery sleep when compared to control subjects. The studies suggest that sleep deprivation in both MM subjects and cocaine-dependent subjects is characterized by greater changes in brain ATP levels than control subjects. Greater enhancements in brain ATP following recovery sleep may reflect a greater disruption to or impact of sleep deprivation in drug dependent subjects, whereby sleep restoration processes may be unable to properly regulate brain ATP and maintain brain high-energy equilibrium. These studies support the notion of a greater susceptibility to sleep loss in drug dependent populations. Additional sleep studies in drug abusing populations are needed, particularly those that examine potential differential effects of sleep deprivation.